Effectiveness of 1-year treatment with long-acting formulation of aripiprazole, haloperidol, or paliperidone in patients with schizophrenia: retrospective study in a real-world clinical setting - Di Lorenzo R (Dove Medical Press, 2019)
Rosaria Di Lorenzo,1 Paola Ferri,2 Michela Cameli,3 Sergio Rovesti,4 Chiara Piemonte5 1Psychiatric Intensive Treatment Facility, Department of Mental Health and Drug Abuse, AUSL Modena, Modena, Italy; 2Department of Biomedical, Metabolic and Neural Sciences, University of Modena and Reggio Emilia, Modena, Italy; 3Private Accredited Psychiatric Hospital, Villa degli Ulivi, Caserta, Italy; 4Department of Biomedical, Metabolic and Neural Sciences, University of Modena and Reggio Emilia, Modena, Italy; 5Private Accredited Psychiatric Hospital, Villa Igea, Modena, Italy Background: Schizophrenia is a chronic mental illness that requires lifelong antipsychotic treatment. Therapy discontinuation, often due to poor adherence, increases the risk of relapses after both first and subsequent psychotic episodes. Long-acting injectable (LAI) antipsychotic drugs (APDs) have been introduced to increase therapeutic adherence, reducing blood-level variability compared to corresponding oral preparations. Purpose: To compare the effectiveness of three LAI-APDs: aripiprazole (Apr) prolonged release once monthly (OM) haloperidol decanoate (Hal-D) and paliperidone palmitate (PP-OM). Methods: We retrospectively collected data for all patients with schizophrenia or other psychoses (n=217) treated with the three LAI-APDs for the first time from January 1, 2012 to October 31, 2016: n=48 with Apr-OM, n=55 with Hal-D, and n=114 with PP-OM. After 6 and 12 months of LAI treatments, we assessed clinical and functioning improvement, urgent consultations, psychiatric hospitalizations, adverse effects, and dropout. We compared urgent consultations and psychiatric hospitalizations required by the same patient 6 and 12 months before and after LAI implementation. Data were statistically analyzed. Results: The three LAI groups differed significantly only for “need for economic support from social service” (more frequent in the Hal-D group) and “schizoaffective disorder” (prevalent in the Apr-OM group). Apr-OM was prescribed at the maximum dose required by the official guidelines, whereas the other two LAIs were prescribed at lower doses. After 6 and 12 months’ treatment with the three LAI-APDs, we registered similar and significant reductions in both urgent consultations and psychiatric hospitalizations (P<0.001) and overlapping clinical and functioning improvement-scale scores (P<0.001), and 14.28% of patients dropped out, with no difference among the three LAI-APDs. Different kinds of adverse effects, though similar for number and severity, were reported in the three LAI groups. Conclusion: Our results suggest that both first- and second-generation LAI-APDs represent important therapeutic options, useful for improving schizophrenia’s clinical course and its economic burden. Our study, which offers a wide and comprehensive observation of real-world clinical settings, combined an effectiveness evaluation through mirror analysis performed for each individual patient to a subsequent comparison among the three LAI-APDs, allowing us a more complete evaluation of clinical efficacy. Keywords: paliperidone palmitate once monthly, haloperidol decanoate, aripiprazole prolonged release once monthly, schizophrenia relapses and clinical course, long-acting treatment effectiveness, first-generation antipsychotics, second-generation antipsychotics